Increase of β2-integrin on adhesion of THP-1 cells to collagen vitrigel membrane. Issue 11 (1st November 2016) - Uchino, Tadashi; Kuroda, Yukie; Ishida, Seiichi; Yamashita, Kunihiko; Miyazaki, Hiroshi; Oshikata, Ayumi; Shimizu, Kumiko; Kojima, Hajime; Takezawa, Toshiaki; Akiyama, Takumi; Ikarashi, Yoshiaki
Abstract: When human monocyte-derived leukemia (THP-1) cells, which are floating cells, are stimulated with lipid peroxides, or Streptococcus suis, these cells adhere to a plastic plate or endothelial cells. However, it is unclear whether or not non-stimulated THP-1 cells adhere to collagen vitrigel membrane (CVM). In this study, firstly, we investigated the rate of adhesion of THP-1 cells to CVM. When THP-1 cells were not stimulated, the rate of adhesion to CVM was high. Then, to identify adhesion molecules involved in adhesion of THP-1 cells to CVM, expressions of various cell adhesion molecules on the surface of THP-1 cells adhering to CVM were measured. β-actin, β-catenin, and β1-integrin expressions did not change in non-stimulated THP-1 cells cultured on CVM compared with those in cells cultured in a flask, but β2-integrin expression markedly increased. Graphical abstract: : THP-1 cells were seeded in T-75, or CVM, or CVM added PMA 10 ng/mL; and β-actin(A), β-catenin(B), β1-integrin(C) and β2-integrin(D) expression were measured ( N  = 3).